A case study of wind turbine rotor over-speed fault diagnosis using combination of SCADA data, vibration analyses and field inspection. (April 2023) - Morshedizadeh, Majid; Rodgers, Marianne; Doucette, Andre; Schlanbusch, Peder
Graphical abstract: Highlights: A comprehensive wind farm data strategy is outlined. Environmental and operational conditions are investigated and novel per- formance indicators for various components are introduced. Financial assessment is performed and a modified operation strategy is introduced and successfully experimented. Abstract: Reduction of wind turbines down times is paramount in wind energy develop- ment and cost effectiveness. Such reductions require early fault detection and more importantly, a comprehensive Root Cause Analysis (RCA) to completely fix at risk component(s). Given the complexity of wind turbines (and their con– trol systems) and the chaotic environment in which they operate, such a goal is difficult to obtain in many cases. This paper presents a successful case study that combines data analysis approaches with deep knowledge of wind turbine operation. It is shown how occurrence of over speed faults which normally hap- pen during gusty winds (i.e. high turbulent intensity) can be due to a bearing slipping issue in the gearbox. An integrated high-frequency vibration analyses, gearbox oil particle count, and 1 Hz operational and meteorological data min- ing approach, in addition to site inspection create a very suitable path towards establishment of a reliable operational strategy and repairs in a timely manner. A financial and operation strategy that demonstrates the proposed short- and long-term solutions is also presented.